Neural architectures of music – Insights from acquired amusia - Sihvonen A.; Särkämö T.; Rodríguez-Fornells A.; Ripollés P.; Münte T.; Soinila S. (Elsevier Ltd, 2022)
The ability to perceive and produce music is a quintessential element of human life, present in all known cultures. Modern functional neuroimaging has revealed that music listening activates a large-scale bilateral network of cortical and subcortical regions in the healthy brain. Even the most accurate structural studies do not reveal which brain areas are critical and causally linked to music processing. Such questions may be answered by analysing the effects of focal brain lesions in patients´ ability to perceive music. In this sense, acquired amusia after stroke provides a unique opportunity to investigate the neural architectures crucial for normal music processing. Based on the first large-scale longitudinal studies on stroke-induced amusia using modern multi-modal magnetic resonance imaging (MRI) techniques, such as advanced lesion-symptom mapping, grey and white matter morphometry, tractography and functional connectivity, we discuss neural structures critical for music processing, consider music processing in light of the dual-stream model in the right hemisphere, and propose a neural model for acquired amusia.